Stress and Response to Treatment: Insights From a Pilot Study Using a 4-week Contemplative Self-Healing Meditation Intervention for Posttraumatic Stress in Breast Cancer - Emanuela Offidani PhD; Janey C. Peterson EdD, MS; Joseph Loizzo MD, PhD; Anne Moore MD; Mary E. Charlson MD (SAGE Publishing, 2017)
Along with symptoms of anxiety and depression, many breast cancer survivors experience symptoms of posttraumatic stress disorder (PTSD) that may worsen in the setting of other stressful life events. The aim of this pilot study was to evaluate whether a 4-week version of our Contemplative Self-Healing program would have different effects in reducing PTSD symptoms between breast cancer survivors with or without chronic stress at baseline. PTSD symptoms were measured using the Impact of Events scale (IES). A linear mixed model analysis was used to evaluate within patients changes in IES score. Results showed that breast cancer patients who were experiencing chronic stress reported greater improvement in IES score than those without chronic stress. Our preliminary findings shed light on the need to evaluate life stressors in breast cancer patients. Evaluating chronic stress may be essential in predicting which cancer patients may benefit most from a psychological intervention.